2021
DOI: 10.1002/jclp.23281
|View full text |Cite
|
Sign up to set email alerts
|

Rumination as a widespread emotion‐based cognitive vulnerability in borderline personality disorder: A meta‐analytic review

Abstract: Objective The current quantitative review aims at comprehensively clarifying the role of rumination in borderline personality disorder (BPD) considering its relevance for several clinical models of the disorder. Method This meta‐analysis included 29 independent studies assessing different forms of rumination—general tendency to engage in ruminative thinking patterns and four types of emotion‐based rumination among both nonclinical subjects reporting BPD features and patients with BPD. Furthermore, the study te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 117 publications
(135 reference statements)
1
8
0
1
Order By: Relevance
“…A meta‐analysis of 3,543 participants 173 found that BPD symptomatology was associated with less frequent use of adaptive emotion regulation strategies (i.e., cognitive reappraisal, problem solving, and acceptance) and more frequent use of maladaptive ones (i.e., suppression, rumination, and avoidance). The role of rumination as a dysfunctional emotion regulation strategy in BPD was also confirmed by two recent meta‐analyses 174,175 . Furthermore, a meta‐analysis found stronger self‐report of experienced shame in comparison to healthy controls, with a large effect size of d=1.44 (n=10, N=3,543) 176 .…”
Section: Social Cognition and Neurocognitionmentioning
confidence: 70%
“…A meta‐analysis of 3,543 participants 173 found that BPD symptomatology was associated with less frequent use of adaptive emotion regulation strategies (i.e., cognitive reappraisal, problem solving, and acceptance) and more frequent use of maladaptive ones (i.e., suppression, rumination, and avoidance). The role of rumination as a dysfunctional emotion regulation strategy in BPD was also confirmed by two recent meta‐analyses 174,175 . Furthermore, a meta‐analysis found stronger self‐report of experienced shame in comparison to healthy controls, with a large effect size of d=1.44 (n=10, N=3,543) 176 .…”
Section: Social Cognition and Neurocognitionmentioning
confidence: 70%
“…Moreover, people who engage in NSSI frequently have genetic predispositions toward higher emotional reactivity to negative emotions (Groschwitz & Plener, 2012). Disorders such as depression and BPD that are associated with high levels of rumination (Cavicchioli & Maffei, 2021;Mor & Winquist, 2002) are also associated with poorer impulse control due to impaired frontal lobe function (Husain et al 2019). It is possible that neuroticism is the common factor underlying the relationship between rumination and engagement in NSSI.…”
Section: Discussionmentioning
confidence: 99%
“…For example, rumination‐focused cognitive‐behavioral therapy (RF‐CBT; Watkins et al, 2007 ) was created to help clients recognize and find strategies to quell ruminative thinking patterns. Future research should investigate whether one mechanism by which treatments shown to be effective at decreasing NSSI (such as DBT; Chen et al, 2021 ) do so is through reducing rumination. Additionally, future research should examine whether rumination‐focused treatments like RF‐CBT are effective in decreasing instances of NSSI.…”
Section: Discussionmentioning
confidence: 99%
“…Although the results and psychometric properties are promising, future studies should evaluate the psychometric properties of these items in clinical samples. Indeed, given the transdiagnostic nature of rumination across many different disorders (Aldao et al, 2010;Cavicchioli & Maffei, 2021;Hsu et al, 2015;Smith et al, 2018;Szabo et al, 2017), it is essential to verify that the ESM items perform similarly in various clinical samples. Moreover, this study only investigated the psychometric properties of the French ESM protocol with native French-speaking participants.…”
Section: Discussionmentioning
confidence: 99%